The CPA Examination: Volume 1-Practice, Auditing and Theory and the CPA Examination: Volume 2-Suggested Solutions (Book Review). - Burns, Thomas J.; Flesher, Dale L. (The Accounting Review, 1979)
Abstract Reviews the book "The CPA Examination," vol. 1, "Practice, Auditing and Theory," and vol. 2 "Suggested Solutions," by John Anderson and Robert Lentilhon.